Smear Layer Removal in the Apical Third of Root Canals by Two Chelating Agents and Laser: A Comparative in vitro Study - Ashraf, Hengameh; Asnaashari, Mohammad; Darmiani, Soheila; Birang, Reza (Iranian Endodontic Journal, 2014)
Introduction: Smear layer (SL) is produced as a result of mechanical instrumentation of the canal(s). Despite the controversies regarding its removal, the evidence-based trend has shifted towards removing and eliminating the SL. Different methods have been used to remove the SL and the aim of this in vitro study was to evaluate the ability of 17% ethylenediaminetetraacetic acid (EDTA), 18% etidronate and Er: YAG on effective removal of the SL. Methods and Materials: Fifty straight single-rooted teeth were divided into three experimental groups (n=15) and one control group of five. The canals were instrumented with HERO 642 rotary files up to 30/0.06. In group 1, canals were irradiated with Er: YAG laser; in groups 2 and 3, canals were irrigated with 17% EDTA and 18% etidronate, respectively. In group 4 (control) distilled water was used for canal irrigation. The amount of remaining SL was quantified according to Hulsmann’s method with scanning electron microscopy (SEM). Data was analyzed by the Kruskal-Wallis and Mann-Whitney U tests (P<0.05). Results: The results showed statistically significant differences in terms of SL removal among the groups (P<0.05). The amount of removed SL by EDTA was significantly greater followed by Er: YAG laser and 18% etidronate. Conclusion: Within the limitations of this study, EDTA was more effective in removing SL compared to Er: YAG and etidronate.